A Literary Shadow Study - Amanda Wall (MDPI AG, 2022)
A shadow study can be an effective way to consider a student's experience in school. For teacher candidates, engaging in a shadow study can be a responsive approach supporting growing habits of translating theory into practice and making connections among course concepts, research, theory, and principles. When middle-level teacher candidates were unable to have field experiences in recent semesters due to COVID-19, they instead took part in a literary shadow study of a character in a novel for young adolescents. After taking running notes while reading, they connected aspects of the character (including thoughts, words, and actions) to research and principles about education for young adolescents. This was a collective case study to determine overall themes across two cohorts of teacher candidates' shadow studies. Each candidate's literary shadow study was a source of data, analyzed through discourse analysis. The AMLE standards for middle level teacher preparation were start codes; other codes were identified through data analysis. This study builds on the scant research on the shadow study procedure and presents evidence of teacher candidates' learning about young adolescent development as well as middle level structures, and how they connect these ideas to specific student experiences (in this case, fictional) and their own identities as teachers.